Pemanfaatan Biochar dan Respon Pertumbuhan Tanaman Sawi Hijau (Brasicca juncea L) pada Tanah Tercemar Merkuri (Hg): Utilization of Biochar and Growth Response of Green Mustard Plant (Brasicca juncea L) on Mercury (Hg) Polluted Soil - Rohmaniati, Baiq Siti; Sukartono, Sukartono; Fahrudin, Fahrudin; Kusnarta, I Gusti Made; Susilowati, Lolita Endang (LPPM Universitas Mataram, 2023)
This study aims to determine the potential of biochar on the mobility of mercury (Hg) in polluted soil planted with mustard greens (Brasicca juncea) and to determine the growth response of mustard greens (Brasicca juncea) in absorbing mercury (Hg). This study used the experimental method, which is a method that aims to examine the effect of biochar application at various doses on the mobility of mercury using the indicator plant mustard greens (Brasicca juncea L) in mercury (Hg) polluted soil. This experiment was carried out from March to June 2023 in the Greenhouse of the Faculty of Agriculture, University of Mataram. Soil samples were collected in Pelangan Village, Sekotong District, West Lombok Regency at several points near the gold processing unit. The samples were taken at top soil of 30 cm with a distance of 100 cm from the processing site then composited. Soilschemical properties including concentration of Hg before and after experiments were measured. Agronomic variables include fresh and dry weight of roots, total dry weight of and concentration of Hg) in plant tissue were also measured. The results of the study showed that the application of rice biochar reduced mobility of Hg in soils. The concentration of extractable-Hg in biochar-treated soils were lower compared to control. This is likely related to the potential adsorption of a number of IHg and MeHg by the negative surface of the biochar and also the formation of association of Hg bonds with the functional groups of the biochar. However, this needs further confirmation.